Primary school students' perceptions and developed artefacts and language from learning coding and computational thinking using the 3C model - Martin, David A.; Curtis, Peter; Redmond, Petrea (Journal of computer assisted learning, 2024)
Background A resurgence in teaching coding in primary school classrooms has led to a pedagogical swing towards using physical computing and coding to develop students' use of algorithms, computational thinking, and problem‐solving skills. Two obstacles impede the optimal development of these objectives: the availability of a suitable pedagogy and an instructional sequencing model for primary school teachers to effectively present coding and computational thinking concepts and skills to students in alignment with their developmental stage. Objective This study aims to address both obstacles by introducing the 3C Model, a newly developed instructional sequence grounded in established pedagogies and designed to effectively teach coding and computational thinking skills to primary school students based on their developmental stage. Methods The qualitative study employed two data sources to triangulate findings, using: (1) semi‐structured interviews and thematic analysis to investigate 11 primary school students' perceptions of their learning experiences with the 3C Model, and (2) researcher observations along with reflections of the students' developed and demonstrated learning through the method of knowing‐in‐action, reflection‐in‐action, and reflection‐on‐action. Results and Conclusions The findings of this study fill a gap in the existing literature by demonstrating that the pedagogical and sequential approach embedded in the 3C Model not only enhanced students' engagement levels but also resulted in improved curriculum learning outcomes. The 3C Model provides teachers with a coherent and age‐appropriate instructional structure. It uses physical computing devices and digital coding platforms to introduce coding concepts, furthering the development of computational thinking skills in primary school students beyond mere procedural and rote learning. Implications The study holds important implications for practical applications, as it addresses an absence in the literature of an established pedagogy and instructional sequencing model for effectively teaching coding and computational thinking concepts and skills to primary school students. Drawing on established pedagogical and developmental learning theories, the 3C Model provides primary school teachers with an engaging, age‐appropriate instructional method that avoids decontextualised teaching and surface‐based learning. Instead, it encourages collaborative student work and contextualised learning, steering away from isolated and generic approaches. Lay Description What is currently known about this topic Teaching coding and computational thinking concepts and skills is complex due to their nature. Teaching resources such as work samples, curriculum connections and tools are available to primary school teachers. There is no consensus on the most effective methods to teach these concepts and skills. Primary school teachers default to applying general teaching strategies due to the lack of an age‐appropriate, specific activity sequencing model to use during coding instruction. What does this paper add The study fills the existing gap by presenting a newly conceptualised instructional model, which considers the students’ developmental stage of learning and pedagogical best practices. The study trialled the 3C Model with primary school students in a classroom setting. The study found that employing the pedagogical approach of the 3C Model increased students’ engagement levels and resulted in enhanced curriculum learning outcomes. Implications for practitioners Without an age‐appropriate instructional sequencing model students may not be grasping the underlying concepts. Simply focusing on the code without emphasising concepts such as decomposition and algorithmic thinking will result in shallow learning. Key considerations in using the 3C Model are ensuring that conceptual development occurs using physical computing devices and language students are familiar with prior to introducing coding language and its symbolic representations. Primary school teachers should consider incorporating physical interactive digital devices, physical movement, staged language development and subsequent coding procedures within the context of an engaging and authentic problem. This approach enables students to effectively grasp and represent coding and computational thinking concepts and skills, surpassing mere procedural and rote learning.